Achieving Competitive Advantage From Industry and Resource-Based Perspectives: A Study in Private Hospitals (Third Sector Social Economic Review, 2026)
The strategic management literature has long debated how firms achieve competitive advantage. Within this context, two fundamental perspectives stand out: the industry-based view, which attributes competitive advantage to the structure of the industry, and the resource-based view, which emphasizes the firm’s unique resources and capabilities. In the healthcare sector, competition has become increasingly pronounced due to the rise of private hospitals, globalization, and growing expectations regarding service quality. The aim of this study is to determine which of these perspectives better explains the competitive advantage of private hospitals. Data were collected from 402 healthcare professionals employed in private hospitals in Ankara and analyzed using confirmatory factor analysis, correlation analysis, and structural equation modeling. The findings indicate that the most influential industry forces affecting competitive advantage are patients’ bargaining power and the intensity of competition. In terms of firm-specific resources, corporate reputation and brand strength emerged as the most significant factors. Model analyses revealed that firm-specific resources have a substantially stronger impact on both general competitive strategies and hospital performance compared to industry forces. The indirect effects of general competitive strategies were found to be statistically insignificant. Overall, the results demonstrate that the resource-based view plays a more dominant role in explaining competitive advantage in private hospitals.
Keywords: Strategic Management; Competition power; Competetive Advantage; industry based view; resource based view